ICT and Productivity: A Review of the Literature - Federico Biagi (European Commission, Joint Research Centre (JRC), 2013)
In this report we review the literature on the relationship between ICT and productivity. In Sect. 1 we discuss in broad terms the theoretical relationship between ICT and productivity, while in Sect. 2 we present the growth accounting methodology, which tries to measure the contributions to growth from difference sources (ICT and non ICT capital, human capital, total factor productivity). Within the growth-accounting methodology, in Sect. 3, we discuss the U.S. - E.U. productivity gap and the role of ICTs, and we show that the latter are responsible for the U.S. acceleration in productivity growth observed in the period 1996-2006 and for the widening of the U.S. – E.U. productivity gap in the same period. Then, in Sect. 4, we move to regression based studies, and we review the literature that uses macro, meso (sectoral) and firm/plant level data. While the overall message on the importance of ICT for growth coming from this literature is consistent with the findings of the studies based on growth accounting, the econometric approach allows researchers to investigate a wider set of questions. In particular, we focus on the role of ICT as a General Purpose Technology aspects and we review the literature studying the role of ICT and complementary assets in firms' productivity and the literature exploring the positive externalities related to ICT capital and the impact of ICT usage on the innovative capability of firms. Finally, we also review the literature on the relationship between ICT infrastructures and GDP growth.
Keywords: D22; D24; E01; O30; O47; 330; ICT; labour productivity; total factor productivity; innovation